Pleasure of paying when using mobile payment: Evidence from EEG studies - Wang, Manlin; Ling, Aiqing; He, Yijin; Tan, Yulin; Zhang, Linanzi; Chang, Zeyu; Ma, Qingguo (Frontiers in Psychology, 2022)
Mobile payment has emerged as a popular payment method in many countries. While much research has focused on the antecedents of mobile payment adoption, limited research has investigated the consequences of mobile payment usage relating to how it would influence consumer behaviors (e.g., purchase intention or willingness to pay). Here, we propose that mobile payment not just reduces the “pain of paying,” a traditional view explaining why cashless payment stimulates spending, but it also evokes the “pleasure of paying,” raising from the enhanced processing fluency in completing transactions. We tested this new conceptualization of “pleasure of paying” using EEG, complementing other behavioral measures. In two studies, we found that mobile payment effectively enhanced purchase likelihood (study 1, N = 66) and such an enhancement is generalizable to both hedonic and utilitarian products (study 2, N = 29). By employing EEG measures, we provided the first neural evidence of “pleasure of paying” in addition to the signal of “pain of paying.” Critically, we demonstrated that the “pleasure of paying” is a distinctive psychological mechanism that is induced by mobile payment usage and that the “pleasure of paying” joins the “pain of paying” to mediate the increased purchase intention. We discuss the contributions and implications of these results to the ongoing evolution of cashless payment societies.